2021
DOI: 10.1111/1749-4877.12580
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fertility versus mortality control on the demographics of Mastomys natalensis in maize fields

Abstract: The multimammate mouse, Mastomys natalensis, is the most common rodent pest species in sub-Saharan Africa. Currently, rodenticides are the preferred method used to reduce the population of rodent pests, but this method poses direct and indirect risks to humans and other non-target species. Fertility control is a promising alternative that has been argued to be a more sustainable and humane method for controlling rodent pests. In this study, we compared the effectiveness of fertility control bait EP-1 (quinestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Since the report by Zhang et al ., 13 the anti‐fertility effect of EP‐1 on wild rodents has been confirmed by many laboratory and field studies 15,17–19,21,36,38–40 . In this study, we found EP‐1 and iEP‐1 significantly reduced the weight of testis and epididymis of male long‐tailed hamster, Mongolian gerbils, and mid‐day gerbils, increased the weight of the uterus while inducing uterus oedema, similar to previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Since the report by Zhang et al ., 13 the anti‐fertility effect of EP‐1 on wild rodents has been confirmed by many laboratory and field studies 15,17–19,21,36,38–40 . In this study, we found EP‐1 and iEP‐1 significantly reduced the weight of testis and epididymis of male long‐tailed hamster, Mongolian gerbils, and mid‐day gerbils, increased the weight of the uterus while inducing uterus oedema, similar to previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…One example in this issue is the first laboratory study of the effects of E, P and EP-1 on the subterranean rodent, the plateau zokor (Eospalax baileyi), a key native species competing with livestock on the Qinghai−Tibet plateau (Kang et al 2022). The early field results using EP-1 for management of the multimammate rat in Tanzania (Imakando et al 2021), and the striped field mouse in China (Chen et al 2021), also reported in this special issue, are promising. Larger areas of treatment and more replication in field situations are required to see if this research can lead to successful broad scale management of various pest rodents.…”
Section: Fertility Control Of Rodent Pests: Recent Developments From ...mentioning
confidence: 75%
“…The early field results using EP‐1 for management of the multimammate rat in Tanzania (Imakando et al . 2021), and the striped field mouse in China (Chen et al . 2021), also reported in this special issue, are promising.…”
mentioning
confidence: 99%
“…Field trials at management scale (e.g. Imakando et al 2021) should be conducted to compare baiting strategies (burrow baiting, bait stations, broadcast) regarding their suitability for delivering effective doses to target species and minimizing uptake by nontargets. Bait markers seem a suitable tool for such studies (Jacoblinnert et al 2021).…”
Section: Species Specificity Of Anti-fertility Agents and Environment...mentioning
confidence: 99%